Contrasting Birth Preferences to Practices in El Paso, Texas - Curtis, Rachel S.; Vadney, Regina; Heckert, Carina; Román, Cathy (Frontiers in Global Women's Health, 2022)
Despite calls for increased access to midwifery and a reduction in unnecessary labor interventions by the World Health Organization, the American College of Obstetrics and Gynecologists, and the American Public Health Association, for many birthing parents in the United States, this model remains out of reach. Only 10% of U.S. births are attended by midwives [1], and in Texas, which leads the nation in maternal morbidity and mortality [2], that number is less than 7%. This study examines an unmet demand for personalized, low-intervention midwifery care in El Paso, Texas and the surrounding area through surveys and focus groups aimed at exploring women’s perceptions of their birthing experiences and access to different models of perinatal care. Resulting data suggests a high level of satisfaction with midwifery among those who were able to access it, while those who had used obstetric care often reported limited options and feelings of trauma.